Smart Attendance System for Schools and Organizations Using Image Processing of Live Video - B. , Balachandar; V.D. , Ambeth Kumar; V. , Sathya Preiya; G. , Saranya; S. , Sharmila; K. , Vengatesan; Kumar, Abhishek (International Journal of Psychosocial Rehabilitation, 2020)
It is mandatory to know about the presence of a person/student in a school or organization to have an idea of the number of persons attending/not attending the session before starting. This can be achieved by managing proper attendance. Attendance can also be used to find the number of days worked by an employee in a month for calculating their wages/salary. Even now many schools, colleges, and organizations practice the process of manual attendance. This manual attendance consumes time and paper. To overcome this, we can use a smart attendance system that can take attendance using real-time images. To develop a smart attendance management system that can manage attendance automatically using live video via webcam. A webcam is placed in front of the board, which records a live video. Which is then processed to find the identity of a person using image processing techniques, and then it is checked with a registered dataset/database. It can reduce time. Consumption of paper can be minimized. This system gives info about their ward to parents. This system also helps in evaluating the attendance eligibility criteria of students.